Interactive construction of SPARQL queries using a schema-based graphical interface - Sotiriadis, Ioannis (My University, 2013)
This Master thesis presents a visual querying interface, the Visual Navigator (VN), implemented for Semantic Web. VN is a tool that takes an RDF schema and creates an interactive Entity-Relationship diagram. The user of the tool can interact with the E-R diagram and create SPARQL queries incrementally. After creating the query, the user can submit it and get the results. The results are presented in a table in which result values can be highlighted to automatically add and refine selection criteria in follow-on queries. The resulting system o ers a new way to query the Semantic Web which is different to RDF browsers or query interfaces that are based on graphs of RDF triples.
Keywords: Data- och informationsvetenskap; Computer and Information Science